Anode for non-aqueous electrolyte storage element, non-aqueous electrolyte storage element, and method for manufacturing the same

A carbon particle-based negative electrode with alkaline metal salts and cellulose derivatives addresses the low-temperature performance issue in non-hydrogen electrolyte storage elements by enhancing ion absorption and reducing resistance.

JP7622628B2Active Publication Date: 2025-01-28GS YUASA CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021511485
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2020-03-24
Publication Date
2025-01-28
Estimated Expiration
2040-03-24

AI Technical Summary

Technical Problem

Existing non-hydrogen electrolyte storage elements, such as lithium-ion batteries, suffer from inadequate input performance at low temperatures due to the presence of cellulose derivatives like CMC, which increase electrical resistance.

Method used

A negative electrode composed of carbon particles with a particle size D50 or less, cellulose derivatives, and alkaline metal salts is used to enhance input performance by facilitating efficient alkaline metal ion absorption and reducing electrical resistance.

Benefits of technology

The proposed negative electrode design improves input performance at low temperatures by minimizing electrical resistance through porous cellulose derivative formation and efficient alkaline metal ion absorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622628000004
    Figure 0007622628000004
  • Figure 0007622628000005
    Figure 0007622628000005
  • Figure 0007622628000001
    Figure 0007622628000001
Patent Text Reader

Abstract

One aspect of the present invention is a negative electrode for non-aqueous electrolyte power storage elements, said negative electrode having a negative electrode mixture layer containing: carbon particles with a particle diameter D50 of 7 μm or less; a cellulose derivative; and an alkali metal salt.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode for a nonaqueous electrolyte storage element, a nonaqueous electrolyte storage element, and a method for producing the same. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally include an electrode body having a pair of electrodes electrically isolated by a separator, and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes. In addition, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used as non-aqueous electrolyte storage elements other than secondary batteries.

[0003] The electrodes provided in such nonaqueous electrolyte storage elements generally have a structure in which a mixture layer containing an active material is formed on the surface of a conductive substrate such as a metal foil. It is widely known that the mixture layer of the negative electrode is formed by applying a slurry mixture containing a negative electrode active material such as graphite, a binder such as styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC) as a thickener, and water as a dispersion medium, and then drying the mixture (see Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 2012-18841 Summary of the Invention [Problem to be solved by the invention]

[0005] One of the required properties of non-aqueous electrolyte storage elements is the ability to rapidly charge and discharge. In particular, for hybrid electric vehicles, high input performance at low temperatures is important. However, when the negative electrode mixture contains a cellulose derivative such as CMC, there is a problem that the input performance at low temperatures is insufficient.

[0006] The present invention has been made in light of the above circumstances, and an object of the present invention is to provide a negative electrode for a nonaqueous electrolyte storage element that can improve the input performance of the nonaqueous electrolyte storage element at low temperatures, a nonaqueous electrolyte storage element including this negative electrode, and methods for manufacturing the negative electrode and nonaqueous electrolyte storage element. [Means for solving the problem]

[0007] One embodiment of the present invention made to solve the above problems is a negative electrode for a nonaqueous electrolyte storage element, which has a negative electrode mixture layer containing carbon particles having a particle size D50 of 7 μm or less, a cellulose derivative, and an alkali metal salt.

[0008] Another aspect of the present invention is a method for producing a negative electrode for a nonaqueous electrolyte storage element, comprising applying a negative electrode mixture containing carbon particles having a particle size D50 of 7 μm or less, a cellulose derivative, and an alkali metal salt to a negative electrode substrate.

[0009] Another embodiment of the present invention is a nonaqueous electrolyte electricity storage element including the negative electrode.

[0010] Another aspect of the present invention is a method for producing a nonaqueous electrolyte electricity storage element, comprising the method for producing a negative electrode. Effect of the Invention

[0011] Effects of the Invention According to the present invention, it is possible to provide a negative electrode for a nonaqueous electrolyte storage element that can improve the input performance of the nonaqueous electrolyte storage element at low temperatures, a nonaqueous electrolyte storage element including this negative electrode, and methods for manufacturing the negative electrode and nonaqueous electrolyte storage element. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is an external perspective view showing a secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an electricity storage device formed by assembling a plurality of secondary batteries according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] One aspect of this embodiment is a negative electrode for a nonaqueous electrolyte storage element having a negative electrode mixture layer containing carbon particles having a particle size D50 of 7 μm or less, a cellulose derivative, and an alkali metal salt.

[0014] According to the negative electrode, the input performance of the nonaqueous electrolyte storage element at low temperatures can be improved. The reason why the negative electrode exhibits the above-mentioned effect is presumed to be as follows. In the case where a cellulose derivative is contained in the negative electrode mixture in a conventional negative electrode, it is presumed that the cellulose derivative covers the surface of the negative electrode active material in a film-like manner, thereby increasing the electrical resistance and decreasing the input performance. In contrast, in the negative electrode, the alkali metal ions in the alkali metal salt present on the surface of the carbon particles together with the cellulose derivative are occluded by the carbon particles as the negative electrode potential decreases during charging. In particular, in the present invention, since the particle size D50 of the carbon particles is small, the surface area of ​​the carbon particles is large, and the occlusion of the alkali metal ions occurs efficiently. It is presumed that the occlusion of such alkali metal ions causes voids in the cellulose derivative covering the carbon particles in a film-like manner, and the cellulose derivative is made porous, thereby suppressing the increase in electrical resistance and improving the input performance. However, the interpretation is not limited to this reason alone.

[0015] The "particle size D50" refers to the value (median size) at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50%. Specifically, it can be measured by the following method. Measurements are performed using a laser diffraction particle size distribution analyzer (Shimadzu Corporation's "SALD-2200") and Wing SALD-2200 as measurement control software. A scattering measurement mode is adopted, and a laser beam is irradiated onto a wet cell in which a dispersion liquid in which the measurement sample (carbon particles) is dispersed in a dispersion solvent is circulated, and a scattered light distribution is obtained from the measurement sample. The scattered light distribution is then approximated by a log-normal distribution, and the particle size at which the cumulative degree is 50% is taken as the particle size D50. It has been confirmed that the median size based on the above measurement is almost identical to the particle size D50 measured by extracting 100 carbon particles from an SEM image of the negative electrode, avoiding extremely large and extremely small carbon particles.

[0016] The content of the alkali metal salt per 100 parts by mass of the carbon particles is preferably 0.3 parts by mass or more and 1 part by mass or less. By setting the content of the alkali metal salt within this range, the input performance of the nonaqueous electrolyte storage element at low temperatures can be further improved.

[0017] The alkali metal salt is preferably a sodium salt. By using a sodium salt, the input performance of the non-aqueous electrolyte storage element at low temperatures can be further improved. This is presumably because, compared with the lithium ions constituting the lithium salt generally used as an electrolyte salt, sodium ions are absorbed into the carbon particles at a higher potential, and therefore are absorbed into the carbon particles prior to lithium ions during charging, resulting in efficient formation of a porous membrane-like cellulose derivative.

[0018] The carbon particles are preferably non-graphitizable carbon particles. Non-graphitizable carbon can absorb other alkali metal ions at a potential sufficiently higher than the absorption potential of lithium ions. For this reason, it is presumed that when non-graphitizable carbon particles are used, the formation of the porous film-like cellulose derivative during charging described above occurs more efficiently, and this can further improve the input performance of the non-aqueous electrolyte storage element at low temperatures.

[0019] "Non-graphitizable carbon" refers to carbon that is a material that has an average lattice spacing (d 002 ) of 3.60 Å or more (e.g., 3.60 Å or more and 4.20 Å or less), and is a non-graphitic carbon in which it is difficult to form a graphite structure with three-dimensional stacking order (e.g., it is difficult to convert to graphite even when heated to an ultra-high temperature of around 3300 K under normal pressure). Note that "non-graphitic carbon" refers to a carbonaceous material in which the average lattice spacing (d 002 ) of 3.40 Å or more. The term "discharged state" used here refers to a state in which the open circuit voltage is 0.7 V or more in a single-electrode battery using a negative electrode containing a carbon material as the negative electrode active material as the working electrode and metallic lithium as the counter electrode. In other words, since the potential of the metallic lithium counter electrode in the open circuit state is approximately equal to the redox potential of lithium, the open circuit voltage is approximately equal to the potential of the negative electrode containing a carbon material relative to the redox potential of lithium, and the open circuit voltage of 0.7 V or more means that the potential of the negative electrode is 0.7 V (vs. Li / Li + ) or more, which means that lithium ions capable of being absorbed and released during charging and discharging are sufficiently released from the carbon material, which is the negative electrode active material.

[0020] Another aspect of this embodiment is a method for producing a negative electrode for a nonaqueous electrolyte storage element, comprising coating a negative electrode base material with a negative electrode mixture containing carbon particles having a particle size D50 of 7 μm or less, a cellulose derivative, and an alkali metal salt. According to this method, a negative electrode for a nonaqueous electrolyte storage element that can improve the input performance of the nonaqueous electrolyte storage element at low temperatures can be produced.

[0021] Another aspect of this embodiment is a nonaqueous electrolyte electricity storage element including the negative electrode. The nonaqueous electrolyte electricity storage element includes the negative electrode according to one aspect of the present invention, and therefore has high input performance at low temperatures.

[0022] Another aspect of this embodiment is a method for producing a nonaqueous electrolyte electricity storage element that includes the method for producing a negative electrode. The method makes it possible to produce a nonaqueous electrolyte electricity storage element that has high input performance at low temperatures.

[0023] <Negative electrode> A negative electrode according to one embodiment of the present invention includes a negative electrode substrate and a negative electrode mixture layer laminated on the negative electrode substrate directly or via an intermediate layer. The negative electrode is used as a negative electrode for a non-aqueous electrolyte storage element such as a non-aqueous electrolyte secondary battery.

[0024] (Negative electrode substrate) The negative electrode substrate is a substrate having electrical conductivity. Metals such as copper, nickel, stainless steel, and nickel-plated steel or alloys thereof are used as the material of the negative electrode substrate, and copper or a copper alloy is preferred. The negative electrode substrate may be formed in the form of a foil, a vapor deposition film, or the like, and foil is preferred from the viewpoint of cost. That is, copper foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0025] (Middle class) The intermediate layer is an arbitrary layer that exists between the negative electrode substrate and the negative electrode mixture layer. The intermediate layer contains conductive particles such as carbon particles to reduce the contact resistance between the negative electrode substrate and the negative electrode mixture layer. The configuration of the intermediate layer is not particularly limited, and can be formed, for example, from a composition containing a resin binder and conductive particles.

[0026] (Negative electrode mixture layer) In one embodiment of the present invention, the negative electrode mixture layer is disposed as the outermost layer of the negative electrode. The negative electrode mixture layer contains carbon particles, a cellulose derivative, and an alkali metal salt. The carbon particles are a component that functions as a negative electrode active material. The cellulose derivative is usually a component that functions as a thickener. The negative electrode mixture layer may contain optional components such as a negative electrode active material other than the carbon particles, a thickener other than the cellulose derivative, a binder, a conductive agent, and a filler, as necessary.

[0027] (carbon particles) The upper limit of the particle diameter D50 of the carbon particles is 7 μm, preferably 6 μm, more preferably 5 μm, further preferably 4.5 μm, and particularly preferably 4 μm. By setting the particle diameter D50 of the carbon particles to the above upper limit or less, the input performance of the nonaqueous electrolyte storage element at low temperatures can be improved. In some embodiments, the particle diameter D50 may be 3.5 μm or less, or 2.5 μm or less. On the other hand, the lower limit of the particle diameter D50 is not particularly limited, but from the viewpoints of productivity, availability, and the like, it is, for example, 0.5 μm, preferably 1 μm, and more preferably 1.5 μm. In some embodiments, the particle diameter D50 may be 2.0 μm or more, or 2.2 μm or more. The technology disclosed herein can be preferably implemented in an embodiment in which the particle diameter D50 of the carbon particles is 0.5 μm or more and 7 μm or less (for example, 0.5 μm or more and less than 7 μm, preferably 2 μm or more and 6 μm or less, more preferably 2 μm or more and 4 μm or less).

[0028] Examples of the carbon particles include graphite particles and non-graphitic carbon particles, and non-graphitic carbon particles are preferred. Examples of the non-graphitic carbon particles include non-graphitic carbon particles and graphitic carbon particles, and non-graphitic carbon particles are preferred. By using such carbon particles, the input performance of the non-aqueous electrolyte storage element at low temperatures can be further improved. The content of non-graphitic carbon particles in the carbon particles is not particularly limited, but the lower limit is, for example, 50% by mass, preferably 70% by mass, more preferably 90% by mass, and even more preferably 99% by mass. This upper limit may be 100% by mass. Examples of non-graphitic carbon include phenol resin baked body, furan resin baked body, furfuryl alcohol resin baked body, cellulose charcoal, charcoal, sugar charcoal, etc. Examples of graphitic carbon include coke and pyrolytic carbon. Examples of the graphite particles include natural graphite particles and artificial graphite particles. Here, natural graphite is a general term for graphite extracted from natural minerals, and artificial graphite is a general term for graphite that is artificially produced. Specific examples of natural graphite particles include flake graphite, lump graphite (flake graphite), and earthy graphite. The graphite particles may be spherical natural graphite particles obtained by spheroidizing flat flake graphite. The graphite particles may also be graphite particles with a coating (e.g., an amorphous carbon coating) on ​​the surface.

[0029] In addition, "graphite" refers to the average lattice spacing (d 002 ) is less than 3.40 Å (e.g., 3.30 Å or more but less than 3.40 Å). "Graphitizable carbon" refers to carbon with an average lattice spacing (d 002 ) is 3.40 Å or more and less than 3.60 Å, and among non-graphitic carbons, it refers to non-graphitic carbon that is likely to form a graphite structure with three-dimensional stacking order (for example, that is likely to be converted to graphite by high-temperature treatment at around 3300 K under normal pressure).

[0030] The content of carbon particles in the negative electrode mixture layer is not particularly limited, but the lower limit is preferably 50 mass%, more preferably 65 mass%, further preferably 80 mass%, and particularly preferably 90 mass%. By making the content of carbon particles equal to or greater than the lower limit, sufficient discharge capacity and conductivity can be ensured. On the other hand, the upper limit of this content can be, for example, 99 mass%.

[0031] The negative electrode mixture layer disclosed herein may contain other negative electrode active materials made of materials other than the carbon particles. Examples of other negative electrode active materials that may be contained in the negative electrode mixture layer include commonly used known materials, such as metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide and Sn oxide; polyphosphate compounds, etc. However, the upper limit of the content of negative electrode active materials other than carbon particles in the negative electrode active material may be preferably 20 mass%, may be preferably 5 mass%, or may be preferably 1 mass%.

[0032] (Cellulose derivatives) The cellulose derivative is a component that functions as a thickener when forming a negative electrode mixture layer by coating, etc. Although the cellulose derivative is not particularly limited, it is considered that the cellulose derivative is usually present in the negative electrode mixture layer so as to cover a part or the entire surface of the carbon particles.

[0033] A cellulose derivative is a compound having a structure in which the hydrogen atom of the hydroxyl group of cellulose is replaced with another group. Examples of the cellulose derivative include carboxyalkyl cellulose (carboxymethyl cellulose (CMC), carboxyethyl cellulose, carboxypropyl cellulose, etc.), alkyl cellulose (methyl cellulose, ethyl cellulose, etc.), hydroxyalkyl cellulose (hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, etc.), cellulose acetate phthalate, hydroxypropyl methyl cellulose phthalate, acetyl cellulose, etc. Among these, carboxyalkyl cellulose is preferred, and CMC is more preferred. The above cellulose derivatives may be used alone or in combination of two or more.

[0034] A part or all of these cellulose derivatives may be present in the form of a salt. Examples of the salt of the cellulose derivative include an alkali metal salt (e.g., a sodium salt) and an ammonium salt. It is preferable that the cellulose derivative is present in the negative electrode mixture layer in the form of an ammonium salt or in the form of no salt, or that the negative electrode mixture layer is formed using a cellulose derivative in the form of an ammonium salt or in the form of no salt. In this case, the input performance at low temperatures is further improved due to the effective absorption of alkali metal ions of the alkali metal salt during charging.

[0035] The content of the cellulose derivative in the negative electrode mixture layer is not particularly limited, but the lower limit is, for example, 0.1% by mass. The lower limit of the content of the cellulose derivative is preferably 0.3% by mass, more preferably 0.5% by mass. On the other hand, the upper limit of the content of the cellulose derivative is, for example, 10% by mass. The upper limit of the content of the cellulose derivative is preferably 5% by mass, more preferably 3% by mass. In some embodiments, the upper limit of the content of the cellulose derivative may be 2% by mass, 1.5% by mass, or 1.2% by mass. By setting the content of the cellulose derivative to the above lower limit or more, sufficient viscosity can be imparted to the negative electrode mixture paste when forming the negative electrode mixture layer, and the negative electrode mixture layer can be efficiently formed. On the other hand, by setting the content of the cellulose derivative to the above upper limit or less, the above-mentioned performance improvement effect (for example, the effect of improving input performance at low temperatures) is better exhibited, and a sufficient amount of carbon particles can be contained in the negative electrode mixture layer, thereby increasing the electric capacity of the nonaqueous electrolyte storage element.

[0036] (alkali metal salts) Although the alkali metal salt is not particularly limited, it is considered that it is usually present on the surface and periphery of the carbon particles together with the cellulose derivative in the negative electrode mixture layer. The alkali metal salt is preferably a salt that is difficult to dissolve in the non-aqueous solvent constituting the non-aqueous electrolyte, and more preferably a salt that is substantially insoluble in the non-aqueous solvent constituting the non-aqueous electrolyte. In addition, it is preferable to use an alkali metal salt that does not significantly affect the pH of the negative electrode mixture described later. Furthermore, it is preferable that the salt is a salt that is difficult to decompose at the reduction reaction potential of the negative electrode. Furthermore, it is preferable that the alkali metal ion constituting the alkali metal salt is a salt that is occluded in the carbon particles at a potential higher than that of the charge carrier. An alkali metal salt that satisfies such conditions can be used without any particular restrictions. In a preferred embodiment, the alkali metal salt is a salt that is substantially insoluble in the non-aqueous solvent constituting the non-aqueous electrolyte. In this case, it is assumed that the alkali metal salt in the negative electrode mixture layer usually exists as a solid (typically particles). The alkali metal salt may be a salt other than the electrolyte salt constituting the non-aqueous electrolyte. In addition, when the cellulose derivative exists as an alkali metal salt, the cellulose derivative is not included in the alkali metal salt. The presence of the alkali metal salt in the negative electrode mixture layer can be confirmed, for example, by analysis using an electron probe micro analyzer (EPMA).

[0037] The alkali metal constituting the alkali metal salt is not particularly limited as long as it is a metal belonging to the first group of the periodic table, and examples thereof include lithium, sodium, potassium, rubidium, and cesium. Among them, it is preferable that it is other than lithium, more preferably sodium and potassium, and even more preferably sodium. That is, among the alkali metal salts, sodium salts are preferable. In the case of an alkali metal salt other than lithium salt, the input performance of the nonaqueous electrolyte storage element at low temperatures can be further improved. This is presumably because alkali metal ions other than lithium salts are absorbed into carbon particles at a relatively high potential, and thus a porous film-like cellulose derivative is efficiently formed.

[0038] The alkali metal salt may be an inorganic salt such as a halide, carbonate, sulfate, or silicate, or an organic salt such as a carboxylate (e.g., acetate, oxalate, propionate, citrate, or glycinate), but inorganic salts are preferred because they are less likely to undergo reductive decomposition during charging and discharging, and halides and sulfates, whose aqueous solutions are in the neutral region, are more preferred, with halides being even more preferred. Examples of halides include fluorides, chlorides, bromides, and iodides, with chlorides being preferred. Specific examples of alkali metal salts include chlorides such as lithium chloride, sodium chloride, potassium chloride, and rubidium chloride; bromides such as sodium bromide and potassium bromide; fluorides such as lithium fluoride, sodium fluoride, and potassium fluoride; nitrates such as lithium nitrate, sodium nitrate, and potassium nitrate; sulfates such as lithium sulfate, sodium sulfate, and potassium sulfate; carbonates such as lithium carbonate, potassium carbonate, potassium bicarbonate, sodium carbonate, and sodium bicarbonate; borates such as sodium borate; and carboxylates such as potassium acetate, sodium acetate, sodium glycolate, and sodium citrate. Among these, preferred forms of alkali metal salts include chlorides of alkali metals such as sodium chloride and potassium chloride, and sodium chloride is particularly preferred. The above-mentioned alkali metal salts may be used alone or in combination of two or more.

[0039] The content of the alkali metal salt is not particularly limited, but the lower limit may be, for example, 0.001 parts by mass relative to 100 parts by mass of carbon particles. The lower limit of the content of the alkali metal salt is, for example, 0.01 parts by mass (for example, 0.05 parts by mass), preferably 0.1 parts by mass, and more preferably 0.3 parts by mass. On the other hand, the upper limit of the content of the alkali metal salt may be, for example, 10 parts by mass relative to 100 parts by mass of carbon particles. The upper limit of the content of the alkali metal salt is, for example, 8 parts by mass, preferably 5 parts by mass, more preferably 2 parts by mass, even more preferably 1 part by mass, and particularly preferably 0.7 parts by mass. By setting the content of the alkali metal salt within the above range, it is possible to further improve the input performance at low temperatures. The technology disclosed herein can be preferably implemented in an embodiment in which the content of the alkali metal salt in the negative electrode mixture layer is 0.1 parts by mass or more and 5 parts by mass or less (preferably 0.3 parts by mass or more and 1 part by mass or less) relative to 100 parts by mass of carbon particles. Here, the content of the alkali metal salt is calculated as follows. That is, the negative electrode before charging / discharging or in a discharged state is immersed in water. The amount of the alkali metal salt (typically the alkali metal ion and / or anion constituting the salt) dissolved from the negative electrode in the water is measured using ion chromatography, inductively coupled plasma (ICP) analysis, etc., to obtain the content of the alkali metal salt. The discharged negative electrode is obtained by dismantling the energy storage device, removing the negative electrode, washing it with dimethyl carbonate (DMC), and then drying it in a vacuum.

[0040] The amount of the alkali metal ion contained in the negative electrode mixture layer is not particularly limited, but the lower limit may be, for example, 0.0002 mmol per 1 g of carbon particles. The lower limit of the amount of the alkali metal salt contained is, for example, 0.002 mmol (for example, 0.01 mmol), preferably 0.02 mmol, and more preferably 0.05 mmol. On the other hand, the upper limit of the amount of the alkali metal ion contained may be, for example, 2 mmol per 1 g of carbon particles. The upper limit of the amount of the alkali metal ion contained is, for example, 1.5 mmol, preferably 1 mmol, more preferably 0.3 mmol, further preferably 0.2 mmol, and particularly preferably 0.1 mmol. By setting the amount of the alkali metal ion contained within the above range, the input performance at low temperatures can be further improved. The technology disclosed herein can be preferably implemented in an embodiment in which the content of alkali metal ions in the negative electrode mixture layer is 0.02 mmol or more and 1 mmol or less (preferably 0.05 mmol or more and 0.2 mmol or less) per gram of carbon particles.

[0041] Although not particularly limited, the ratio (C1 / C2) of the content C1 [mass%] of the alkali metal salt in the negative electrode mixture layer to the content C2 [mass%] of the cellulose derivative is preferably about 10 or less. The above C1 / C2 is preferably 5 or less, more preferably 3 or less, even more preferably 1 or less, and particularly preferably 0.7 or less. With such a ratio (C1 / C2) of the content of the alkali metal salt and the cellulose derivative, the above-mentioned effect can be more suitably exhibited. The lower limit of C1 / C2 is not particularly limited as long as it exceeds 0 (zero), but from the viewpoint of easily exhibiting the effect of this embodiment, it is preferably 0.001 or more, more preferably 0.01 or more, and even more preferably 0.03 or more. In some embodiments, the above C1 / C2 may be, for example, 0.05 or more, or 0.1 or more (for example, 0.3 or more).

[0042] (binder) The binder is a component for fixing carbon particles, etc. As the binder, either an aqueous binder or a non-aqueous binder can be used, but an aqueous binder is preferred. An aqueous binder and a non-aqueous binder may be used in combination.

[0043] The aqueous binder means a binder that can be dissolved or dispersed in an aqueous solvent when preparing a mixture. The aqueous solvent means water or a mixed solvent mainly composed of water. Examples of the solvent other than water that constitutes the mixed solvent include organic solvents (such as lower alcohols and lower ketones) that can be mixed uniformly with water. The non-aqueous binder means a binder that can be dissolved or dispersed in a non-aqueous solvent when preparing a mixture. Examples of the non-aqueous solvent include N-methyl-2-pyrrolidone (NMP).

[0044] As the binder, known binders can be used, for example, polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), vinyl acetate copolymer, styrene butadiene rubber (SBR), acrylic acid modified SBR, ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, fluororubber, gum arabic, polyvinylidene fluoride (PVDF), polyvinylidene chloride (PVDC), polyethylene, polypropylene, polyethylene oxide (PEO), polypropylene oxide (PPO), polyethylene oxide-propylene oxide copolymer (PEO-PPO), etc. Among these, from the viewpoint of binding property and resistance increase suppression property, rubber-based binders such as SBR, acrylic acid modified SBR, EPDM, sulfonated EPDM, fluororubber, and gum arabic are preferred, and SBR is more preferred.

[0045] The lower limit of the binder content in the negative electrode mixture layer is preferably 1 mass %, more preferably 2 mass %. Meanwhile, the upper limit of the binder content is preferably 10 mass %, more preferably 5 mass %. By setting the binder content within the above range, it is possible to further improve the input performance of the nonaqueous electrolyte storage element at low temperatures.

[0046] (Other Ingredients) The conductive agent is not particularly limited as long as it is a conductive material that does not adversely affect the performance of the electric storage device. Examples of such conductive agents include metals, conductive ceramics, etc. The conductive agent may be in the form of powder, fiber, etc.

[0047] The filler is not particularly limited as long as it does not adversely affect the performance of the electricity storage device. Examples of the main component of the filler include polyolefins such as polypropylene and polyethylene, silica, alumina, zeolite, and glass.

[0048] <Method of manufacturing the negative electrode> A method for producing a negative electrode according to one embodiment of the present invention includes applying a negative electrode mixture containing carbon particles having a particle size D50 of 7 μm or less, a cellulose derivative, and an alkali metal salt to a negative electrode substrate.

[0049] The negative electrode mixture (negative electrode mixture layer forming material) is a slurry (paste) in which components such as carbon particles, cellulose derivatives, alkali metal salts, and other binders as necessary are dispersed in a dispersion medium such as water. The negative electrode mixture can be applied to the negative electrode substrate by a known method. This application includes spraying, immersion, and the like. The negative electrode mixture may be applied directly to the surface of the negative electrode substrate, or may be applied to the surface of the intermediate layer of the negative electrode substrate on which the intermediate layer is provided.

[0050] The manufacturing method may further include drying the negative electrode mixture applied to the negative electrode base material. By drying the negative electrode mixture, a negative electrode mixture layer is obtained. This drying may be natural drying or heat drying.

[0051] After the drying, the negative electrode mixture layer may be pressed in the thickness direction in order to improve the adhesion between the negative electrode mixture layer and the negative electrode base material, etc. Through such steps, the negative electrode can be obtained.

[0052] <Non-aqueous electrolyte electricity storage element> The nonaqueous electrolyte storage element according to one embodiment of the present invention has a positive electrode, a negative electrode, and a nonaqueous electrolyte. Hereinafter, a secondary battery will be described as an example of a nonaqueous electrolyte storage element. The positive electrode and the negative electrode are usually stacked or wound alternately with a separator interposed therebetween to form an electrode body. This electrode body is housed in a case, and the nonaqueous electrolyte is filled in the case. The nonaqueous electrolyte is interposed between the positive electrode and the negative electrode. In addition, as the case, a known metal case, a resin case, or the like that is usually used as a case for a secondary battery can be used.

[0053] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode mixture layer laminated on the positive electrode substrate directly or via an intermediate layer. The intermediate layer of the positive electrode may be the same as the intermediate layer of the negative electrode described above.

[0054] The positive electrode substrate has electrical conductivity. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or alloys thereof are used. Among these, aluminum and aluminum alloys are preferred in terms of the balance between potential resistance, high electrical conductivity, and cost. In addition, the positive electrode substrate may be formed in the form of foil, vapor deposition film, etc., and foil is preferred in terms of cost. That is, aluminum foil is preferred as the positive electrode substrate. In addition, examples of aluminum or aluminum alloys include A1085P, A3003P, etc., as specified in JIS-H-4000 (2014).

[0055] The positive electrode mixture layer is formed from a so-called positive electrode mixture containing a positive electrode active material. The positive electrode mixture forming the positive electrode mixture layer further contains optional components such as a conductive agent, a binder, a thickener, and a filler as necessary.

[0056] As the positive electrode active material, various materials that have been conventionally used as positive electrode active materials for lithium ion secondary batteries can be used without any particular limitation. x MO y (M represents at least one transition metal) x CoO2,Li x NiO2,Li x MnO3,Li x NiαCo (1- α ) O2, Li x NiαMnβCo (1- α - β ) Li with spinel crystal structure such as O2 x Mn2O4,Li x NiαMn (2- α ) O4, etc.), Li w Me x (XO y ) z (Me represents at least one transition metal, and X represents, for example, P, Si, B, V, etc.) polyanion compounds (LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc.) in the above formula. The elements or polyanions in these compounds may be partially substituted with other elements or anion species. In the positive electrode mixture layer, one of these compounds may be used alone, or two or more of them may be used in combination.

[0057] The optional components such as the conductive agent, binder, thickener, and filler used in the positive electrode mixture may be the same as those in the negative electrode mixture described above. Carbon particles may also be used as the conductive agent in the positive electrode mixture.

[0058] (Negative electrode) The negative electrode used is the negative electrode according to one embodiment of the present invention described above.

[0059] (Separator) The separator may be made of a material such as woven fabric, nonwoven fabric, or porous resin film. Among these, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of nonaqueous electrolyte retention. As the main component of the separator, a polyolefin such as polyethylene or polypropylene is preferred from the viewpoint of strength, and a polyimide or aramid is preferred from the viewpoint of resistance to oxidation and decomposition. These resins may also be combined.

[0060] (Non-aqueous electrolyte) The non-aqueous electrolyte is usually a solution in which an electrolyte salt is dissolved in a non-aqueous solvent. The non-aqueous electrolyte may contain other components in addition to the non-aqueous solvent and the electrolyte salt. Examples of the other components include various additives that are commonly used as additives for non-aqueous electrolytes for energy storage elements.

[0061] As the non-aqueous solvent, a known non-aqueous solvent that is generally used as a non-aqueous solvent for a general non-aqueous electrolyte for a storage element can be used. As the non-aqueous solvent, cyclic carbonate, chain carbonate, ester, ether, amide, sulfone, lactone, nitrile, etc. can be mentioned. Among these, it is preferable to use at least a cyclic carbonate or a chain carbonate, and it is more preferable to use a cyclic carbonate and a chain carbonate in combination. When a cyclic carbonate and a chain carbonate are used in combination, the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate: chain carbonate) is not particularly limited, but is preferably, for example, 5:95 or more and 50:50 or less.

[0062] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, catechol carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate.

[0063] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diphenyl carbonate.

[0064] The electrolyte salt may be any known electrolyte salt that is commonly used as an electrolyte salt for a general non-aqueous electrolyte for a storage element. Examples of the electrolyte salt include lithium salt, sodium salt, potassium salt, magnesium salt, onium salt, etc., and lithium salt is preferred.

[0065] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having a fluorohydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0066] The lower limit of the content of the electrolyte salt in the nonaqueous electrolyte is preferably 0.1 mol / L, more preferably 0.3 mol / L, and even more preferably 0.5 mol / L, while the upper limit is not particularly limited, but is preferably 2.5 mol / L, more preferably 2 mol / L, and even more preferably 1.5 mol / L.

[0067] As the non-aqueous electrolyte, a solid electrolyte or the like may also be used.

[0068] (Applications, etc.) The nonaqueous electrolyte storage element has excellent input performance at low temperatures. That is, the nonaqueous electrolyte storage element can be rapidly charged even at low temperatures. Therefore, the nonaqueous electrolyte storage element can be used in various applications in which conventional nonaqueous electrolyte storage elements are used, and can be suitably used as a power source for automobiles, particularly hybrid electric automobiles, which require high input performance at low temperatures.

[0069] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> A method for producing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention includes the method for producing the negative electrode described above.

[0070] The nonaqueous electrolyte storage element can be produced by the same method as that for the conventionally known nonaqueous electrolyte storage element, except for the production of the negative electrode. The production method includes, for example, producing a positive electrode, housing the positive electrode and the negative electrode (electrode body) in a case, and injecting the nonaqueous electrolyte into the case.

[0071] <Other embodiments> The present invention is not limited to the above embodiment, and can be embodied in various modified and improved forms in addition to the above embodiment. For example, the negative electrode may further have a coating layer that covers the negative electrode mixture layer, and may have a structure that does not have a negative electrode substrate or an intermediate layer. In the above embodiment, the nonaqueous electrolyte storage element is mainly described as a secondary battery, but other nonaqueous electrolyte storage elements may also be used. Examples of other nonaqueous electrolyte storage elements include capacitors (electric double layer capacitors, lithium ion capacitors), etc.

[0072] FIG. 1 shows a schematic diagram of a rectangular secondary battery 1 which is one embodiment of the nonaqueous electrolyte storage element according to the present invention. The figure is a see-through view of the inside of the container. In the secondary battery 1 shown in FIG. 1, an electrode body 2 is housed in a battery container 3. The electrode body 2 is formed by winding a positive electrode and a negative electrode with a separator interposed therebetween. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 4', and the negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 5'.

[0073] The configuration of the nonaqueous electrolyte storage element according to the present invention is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery (rectangular battery), and a flat battery. The present invention can also be realized as an electricity storage device including a plurality of the nonaqueous electrolyte storage elements. One embodiment of the electricity storage device is shown in FIG. 2. In FIG. 2, an electricity storage device 30 includes a plurality of electricity storage units 20. Each of the electricity storage units 20 includes a plurality of secondary batteries 1. The electricity storage device 30 can be mounted as a power source for automobiles such as electric vehicles (EVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs). EXAMPLES

[0074] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0075] [Example 1] First, a negative electrode mixture was prepared by kneading 100 parts by mass of HC, 1 part by mass of ammonium salt of CMC, 2 parts by mass of SBR, 0.5 parts by mass of NaCl, and water using non-graphitizable carbon (HC: particle size D50 2.3 μm) as carbon particles, which is a negative electrode active material, ammonium salt of CMC, SBR as a binder, and sodium chloride (NaCl) as an alkali metal salt. The negative electrode mixture was applied to the surface of copper foil (thickness 10 μm) as a negative electrode substrate, and dried at 80 ° C. for 30 minutes to form a negative electrode mixture layer, thereby obtaining a negative electrode.

[0076] Positive electrode active material Li 1.1 Ni 1 / 3 Co 1 / 3 Mn 1 / 3A positive electrode having a positive electrode mixture layer containing 93 parts by mass of O2, 4 parts by mass of acetylene black as a conductive assistant, and 3 parts by mass of PVDF as a binder was manufactured. In addition, a non-aqueous electrolyte was prepared by dissolving 1.0 mol / L of LiPF6 in a solvent in which PC, DMC, and EMC were mixed at a volume ratio of 30%:30%:40%. An electrode body was manufactured using the above negative electrode, positive electrode, and a polyethylene separator, and was then housed in a case together with a non-aqueous electrolyte solution, and a predetermined initial charge / discharge treatment was performed to manufacture a secondary battery (non-aqueous electrolyte storage element) of Example 1.

[0077] [Examples 2 to 15, Comparative Examples 1 to 10] Each of the secondary batteries of Examples 2 to 15 and Comparative Examples 1 to 10 was obtained in the same manner as in Example 1, except that the negative electrode active material (carbon particles) of the type and particle size D50 shown in Tables 1 to 3, and the alkali metal salt of the type and amount shown in Tables 1 to 3 were used. In Tables 1 to 3, "HC" indicates non-graphitizable carbon, "SC" indicates graphitizable carbon, and "-" indicates no blend. Some of the examples are shown in multiple tables for comparison.

[0078] [evaluation] The secondary batteries of Examples 1 to 15 and Comparative Examples 1 to 10 were evaluated by the following method.

[0079] (Input performance at low temperatures) Each secondary battery was charged at a constant current of 25°C and 1C up to 4.2V, and then charged at a constant voltage of 4.2V for a total of 3 hours, and then discharged at a constant current of 1C with a cut-off voltage of 2.4V to measure the discharge capacity of each secondary battery. Note that "1C" is a current value that results in the same amount of electricity as the capacity of the secondary battery when a constant current is applied to the secondary battery for 1 hour. Each secondary battery was charged with an amount of electricity that is 75% of the discharge capacity obtained in the above measurement, and then the battery was adjusted to SOC (State Of Charge) of 75%, and then held at -30°C for 4 hours. Thereafter, the current value was set to a constant voltage, and constant voltage charging was performed with an upper limit current of 40C and an upper limit voltage of 4.2V, and the input value at low temperature was calculated by multiplying the current value and voltage value at 1 second from the start of charging, and this was used as the input performance at low temperature. The measured input performance at low temperature is shown in Tables 1 to 3 as a relative value with the value of Example 8 taken as 100%.

[0080] [Table 1]

[0081] [Table 2]

[0082] [Table 3]

[0083] As shown in Table 1, when an alkali metal salt is added to carbon particles having a particle size D50 of 7 μm or less (Examples 1 to 5), the input performance at low temperatures is improved. In particular, the smaller the particle size D50 of the carbon particles, the more the input performance at low temperatures is improved. Furthermore, a comparison between Example 2 and Example 5 shows that, as an alkali metal salt, NaCl has a greater effect of improving input performance than KCl. On the other hand, when no alkali metal salt is added (Comparative Examples 3 to 7), the input performance at low temperatures is poor, even when carbon particles having a small particle size are used.

[0084] Table 2 shows a comparison based on the content of alkali metal salt. It can be seen that the input performance at low temperatures changes depending on the content of alkali metal salt, and that when the content of alkali metal salt is 0.3 parts by mass or more and 1 part by mass or less, the input performance at low temperatures is particularly improved.

[0085] Table 3 shows a comparison of the types of carbon particles that are negative electrode active materials. It can be seen that, regardless of the type of carbon particles, when an alkali metal salt is added to carbon particles with a particle size D50 of 7 μm or less, the input performance at low temperatures improves. It can also be seen that the effect is higher when non-graphitic carbon HC or SC is used than when graphite is used, and the effect is particularly higher when HC is used. [Industrial Applicability]

[0086] The present invention can be applied to nonaqueous electrolyte storage elements, such as nonaqueous electric field secondary batteries used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]

[0087] 1 Secondary battery 2 Electrode body 3 Battery container 4 Positive terminal 4' Positive lead 5 Negative terminal 5' Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. a negative electrode mixture layer containing carbon particles having a particle size D50 of 7 μm or less, a cellulose derivative, and an alkali metal salt; The negative electrode for a non-aqueous electrolyte storage element, wherein the content of the carbon particles in the negative electrode mixture layer is 50 mass % or more.

2. 2. The negative electrode according to claim 1, wherein the content of said alkali metal salt is from 0.3 parts by mass to 1 part by mass based on 100 parts by mass of said carbon particles.

3. 3. The negative electrode of claim 1, wherein the alkali metal salt is a sodium salt.

4. 4. The negative electrode according to claim 1, 2 or 3, wherein the carbon particles are non-graphitizable carbon particles.

5. 5. The negative electrode according to claim 1, wherein the alkali metal salt is a salt that is substantially insoluble in a non-aqueous solvent that constitutes a non-aqueous electrolyte.

6. A method for producing a negative electrode according to any one of claims 1 to 5, comprising the steps of: A method for producing a negative electrode for a non-aqueous electrolyte storage element, comprising: applying a negative electrode mixture containing carbon particles having a particle size D50 of 7 μm or less, a cellulose derivative, and an alkali metal salt to a negative electrode substrate.

7. A non-aqueous electrolyte electricity storage element comprising the negative electrode according to any one of claims 1 to 5.

8. A method for producing a nonaqueous electrolyte storage element, comprising the method for producing a negative electrode according to claim 6.

Citation Information

Patent Citations

  • Binder resin composition for nonaqueous secondary battery electrode, cathode for nonaqueous secondary battery and lithium ion secondary battery

    JP2012018841A

  • Negative electrode material for nonaqueous electrolyte secondary batteries, negative electrode for nonaqueous electrolyte secondary batteries, manufacturing method thereof, and nonaqueous electrolyte secondary battery

    JP2015149224A

  • Nonaqueous electrolyte power storage device and method for manufacturing the same

    JP2018032477A

  • Non-aqueous electrolyte secondary battery and method for producing a non-aqueous electrolyte secondary battery

    WO2017130918A1